Scientific contributions of citizen science applied to rare or threatened animals. Issue 6 (13th October 2022) - Fontaine, Amélie; Simard, Anouk; Brunet, Nicolas; Elliott, Kyle H.
Abstract: Citizen science is filling important monitoring gaps and thus contributing to the conservation of rare or threatened animals. However, most researchers have used peer‐reviewed publications to evaluate citizen science contributions. We quantified a larger spectrum of citizen science's contributions to the monitoring of rare or threatened animals, including contributions to the peer‐reviewed publications, gray literature and to conservation measures (i.e., actions taken as a direct result of citizen science monitoring). We sought to provide broad information on how results of studies of citizen science monitoring is used. We also evaluated factors associated with success of citizen science projects. We conducted a web search to find citizen science projects focusing on rare and threatened species and surveyed citizen science project managers about their contributions and factors influencing their success. The number of projects increased rapidly after 2010. Almost one‐half of the citizen science projects produced at least 1 peer‐reviewed publication, 64% produced at least 1 gray literature publication, and 64% resulted in at least 1 conservation measure. Conservation measures covered a wide range of actions, including management and mitigation plans, modification of threat status, identification and establishment of protected areas, habitat restoration, control of invasive species, captive breeding programs, and awareness campaigns. Longevity, data quality, and collaboration type best explained quantities of all types of scientific contributions of citizen science. We found that citizen science contributed substantially to knowledge advancement and conservation, especially when programs were long term and had rigorous data collection and management standards, and multidisciplinary or transdisciplinary collaborations. Resumen: La ciencia ciudadana contribuye a llenar vacíos en el monitoreo, lo que ayuda a la conservación de animales raros o amenazados. Sin embargo, la mayoría de los investigadores han usado publicaciones revisadas por pares para evaluar las contribuciones de la ciencia ciudadana. Cuantificamos un mayor espectro de las contribuciones de la ciencia ciudadana al monitoreo de animales raros y amenazados, incluyendo las contribuciones a la literatura gris, a las publicaciones revisada por pares y a las medidas de conservación (es decir, las acciones tomadas como resultado directo del monitoreo ciudadano). Buscamos proporcionar información generalizada sobre cómo los resultados de los estudios de monitoreo ciudadano es usado. También evaluamos los factores asociados con el éxito de los proyectos de ciencia ciudadana. Realizamos una búsqueda en línea para encontrar proyectos de ciencia ciudadana enfocados en especies raras o amenazadas y encuestamos a los gestores de estos proyectos sobre sus contribuciones y los factores que influyen sobre su éxito. El número de proyectos incrementó rápidamente a partir de 2010. De los proyectos de ciencia ciudadana, casi la mitad produjo al menos 1 publicación revisada por pares, el 64% produjo al menos una publicación en la literatura gris y el 64% derivó en al menos 1 medida de conservación. Las medidas de conservación abarcaron una gama extensa de acciones que incluyeron planes de gestión y mitigación, modificación del estado de amenaza, identificación y establecimiento de áreas protegidas, restauración del hábitat, control de especies invasoras, programas de reproducción en cautiverio y campañas de concientización. La longevidad, calidad de los datos y el tipo de colaboración explicaron de mejor manera las cantidades de todos los tipos de contribuciones científicas hechas por la ciencia ciudadana. Descubrimos que la ciencia ciudadana contribuyó sustancialmente al avance del conocimiento y la conservación, especialmente cuando los programas eran a largo plazo y contaban con estándares rigurosos de recolección y gestión de datos, y con colaboraciones multi o transdisciplinarias. 【摘要】: 公民科学正在填补监测上的重大空缺, 从而为珍稀或受威胁动物的保护做出贡献。然而, 大多数研究者仅用同行评议文献来评估公民科学的贡献。我们量化了公民科学在监测珍稀或受威胁动物中更大范围的贡献, 包括对同行评议的灰色文献和保护措施(即作为公民科学监测的直接结果而采取的行动)的贡献, 从而为优化使用公民科学监测研究结果提供更多信息。我们还评估了影响公民科学项目成功的因素。本研究通过网络搜索寻找关注珍稀和受威胁物种的公民科学项目, 并访问了项目管理者, 以了解这些项目的贡献以及影响其成功的因素。我们发现, 公民科学项目的数量在2010年后迅速增加。几乎有一半的公民科学项目发表了至少一篇同行评议的文章, 64%的项目发表了至少一篇灰色文献, 还有64%的项目制定了至少一项保护措施。保护措施涵盖的行动十分广泛, 包括管理和减缓影响计划、改变威胁状态、识别和建立保护区、恢复生境、控制入侵物种、圈养繁殖计划和宣传活动。持续时间、数据质量和合作类型能最好地解释公民科学的各类科学贡献的数量。结果表明, 公民科学对知识进步和保护做出了巨大贡献, 特别是长期、有严格的数据收集与管理标准, 以及多学科或跨学科合作的项目。【翻译:胡怡思;审校:聂永刚】